2015
DOI: 10.1093/jac/dkv371
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusdevelops increased resistance to antibiotics by forming dynamic small colony variants during chronic osteomyelitis

Abstract: In all infection models rifampicin was most effective at reducing bacterial loads. In the chronic stage, particularly in the in vivo model, many tested compounds lost activity against persisting bacteria and some antibiotics even induced SCV formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(158 citation statements)
references
References 50 publications
2
141
1
5
Order By: Relevance
“…For example, it is not known if a special antibiotic regimen induces and selects for CO 2 -dependent SCVs or as yet uncharacterized SCVs. Recent experimental research suggests that additional antimicrobial compounds, such as moxifloxacin and clindamycin, promote the formation of SCVs (33). For this review, 46 clinical studies dealing with SCVs were retrieved from the literature, spanning the time frame from 1951 to 2014 (Table 2).…”
Section: Clinical Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it is not known if a special antibiotic regimen induces and selects for CO 2 -dependent SCVs or as yet uncharacterized SCVs. Recent experimental research suggests that additional antimicrobial compounds, such as moxifloxacin and clindamycin, promote the formation of SCVs (33). For this review, 46 clinical studies dealing with SCVs were retrieved from the literature, spanning the time frame from 1951 to 2014 (Table 2).…”
Section: Clinical Infectionsmentioning
confidence: 99%
“…In particular, in bone tissue, bacterial persistence was observed for up to 2 months and was accompanied by a high rate of SCV formation (142). Antibiotic treatment with different compounds was always less effective in the chronic than in the acute stage of the infection (33). (vi) In contrast to systemic treatment, local treatment with high levels of antibiotics over a prolonged time was successfully tested in a chronic osteomyelitis model in rabbits (143).…”
Section: Animal Models For Studying the Formation And Persistence Of mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also showed an association between presence of SCV S. aureus and more rapid pulmonary decline. Small‐colony variant formation also occurs in MRSA but has only been reported in few cases in CF and non‐CF …”
Section: Virulencementioning
confidence: 99%
“…Recent reports have shown that resistance developed during treatment in initially susceptible S. aureus can also be related to dynamic small colony variants. Some antibiotics like clindamycin, moxifloxacin and gentamicin can even induce the latter [47,48] .…”
Section: Antibiotic Treatmentmentioning
confidence: 99%